Essential Oil from Kaempferia angustifolia Rhizome: Chemical Compositions and Antimicrobial Activities - Vipunngeun, Niran; Palanuvej, Chanida; Ruangrungsi, Nijsiri (Journal of Health Research, 2018)
Essential oil hydrodistilled (ca. 0.26%, fresh wt.) from the rhizome of Kaempferia angustifolia Roscoe (Zingiberaceae) was investigated for its chemical compositions by GC-MS analysis. The oil showed at least 30 components which accounted for monoterpenes (66.73%), oxygenated monoterpenes (27.89%), sesquiterpenes (3.49%), oxygenated sesquiterpenes (1.35%) and others (0.54%). The main constituents in the essential oil from rhizome of K. angustifolia were camphene (45.53%), camphor (17.53%), α-pinene (12.22%) and borneol (5.16%). A preliminary antimicrobial activity of the oil was evaluated using agar diffusion method. The oil exhibited moderately active against gram-positive bacterium Staphylococcus aureus ATCC 29213 and gram-negative bacterium Pseudomonas aeruginosa ATCC 27853 (10.63 ± 0.23, 10.03 ± 0.22 mm respectively) whilst no activities on Escherichia coli ATCC 25922, Bacillus subtilis ATCC 6633, Streptococcus faecalis ATCC 29212, Candida albicans ATCC 10231 and Microsporum gypseum.